Alteraciones del estado de ánimo y estrategias de afrontamiento en víctimas de abuso sexual de 7 a 17 años de edad, que acuden a la unidad de atención y peritaje integral de la Fiscalía Provincial de Loja, periodo 2015 - 2016. - Pineda Rojas, Vanessa Romina (2016)
Sexual abuse is a form of child abuse that undermines the physical, emotional and mental wellness of children and adolescents. Therefore, the present research is aimed at determining the mood alterations and confronting strategies to cope with victims of sexual abuse from 7 to 17 years of age, who attend to the Unit of Attention and Comprehensive Assessment of the Provincial Prosecutor of Loja, period 2015 - 2016. The research was descriptive of a cross-sectional type with a quantitative-qualitative approach, for which it was used The application of the Child Depression Inventory, Beck Depression Inventory, Spence Infant Anxiety, and Adaptive Coping Scale for Children and Adolescents. The population was established in the Unit of Attention and Integral Evaluation of the Provincial Prosecutor of Loja, being the sample delimited in 70 victims of sexual abuse. The results show that in Second Childhood 27% manifest depression; 45% have anxiety; being the style of productive confrontation of greater use in a 73%. In the pre-adolescence 45% present depression, in terms of anxiety levels, 68% have anxiety, and 39% of the victims use the unproductive confronting style. Finally, in the middle adolescence, it can be seen that 86% present depression, whereas in anxiety levels, 93%, proving that 82% of them use the style of confronting unproductive. Hence, it is concluded that anxiety-depressive levels in the victims of sexual abuse and the use of unproductive strategies mostly validate the creation and implementation of a psychotherapeutic proposal aimed at the most affected population. Key words: sexual abuse, anxiety, depression, confronting strategies, childhood and adolescence.